Jake Ransom and the Skull King's Shadow - Book 1 - Rollins, James 1961- (New York : HarperCollins Publishers, 2009)
Middle-schooler Jake and his sister Kady are transported by a Mayan artifact to a strange world inhabited by a mix of people from long-lost civilizations who are threatened by prehistoric creatures and an evil alchemist, the Skull King.
Keywords: Space and time -- Fiction; Siblings -- Fiction; Prehistoric animals -- Fiction; Archeology -- Fiction; Mayas -- Fiction -- Antiquities; Native Americans -- Fiction -- Antiquities -- Central America; Fiction; Fiction